MEMBONGKAR REKAYASA TEKSTUAL DALAM IKLAN DJARUM 76 “PENGEN KURUS” MELALUI ANALISIS DEKONSTRUKSI - Herlina Dinata; Cosmas Gatot Haryono (Universitas Bunda Mulia, 2020)
ABSTRACTAmid the increasingly high number of deaths caused by smoking, cigarette industry players continue to aggressively penetrate the market through advertising. The cigarette industry in Indonesia still places advertisements as one of the spearheads of their marketing. Through various media platforms, the cigarette industry delivers their various products to the public. Various interesting content, through various types of stories that are engineered and interesting, the cigarette industry continues to persuade people to smoke. One of the interesting cigarette advertisements is a 76 episode Djarum advertisement